Discovery of New Class of Trypanocidal Compounds Targeting the Energy Metabolism of African Trypanosomes. (4th October 2017) - Balogun, Emmanuel Oluwadare; Inaoka, Daniel Ken; Shiba, Tomoo; Watanabe, Yoh-Ichi; Moore, Anthony; Harada, Shigeharu; Kita, Kiyoshi
Abstract: Background: African trypanosomes are the pathogens that cause sleeping sickness in humans and Nagana in animals. These diseases are fatal, endemic in sub-Saharan Africa and attributed to the underdevelopment of the subregion. Not less than 25, 000 human lives and animals worth 1.5 billion are lost annually to the diseases. There is no vaccine and the available therapeutic options are few and with limited efficacy, prompting the search for new drug candidates. The unique energy metabolism pathway of African trypanosomes is considered a validated rational strategy towards the development of new drugs. Our previous results show that the simultaneous inhibition of the parasites' glycerol kinase (TGK) and alternative oxidase (TAO), two key enzymes for ATP synthesis in the parasites' resulted in trypanosomes death. However, while ascofuranone (AF) is an established TAO inhibitor, there is no known inhibitor for any TGK. The present study was aimed at the discovery of novel TGK inhibitors for co-administration with AF. Methods: Protein X-ray crystallography, computational medicinal chemistry, and enzyme assay approaches was used to conduct large-scale screening of a chemical library. Results: The resulting hits were compounds possessing different structural scaffolds, which potently inhibited TGK up to 50 nM IC50 values. Interestingly, a number of the inhibitors caused the expected improvement in the potency of AF against trypanosome cells, causing a shift in trypanocidal activity of AF (IC50 ) from nanomolar to picomolar concentrations ( P < 0.05). Remarkably, one of the inhibitors was identified as a dual inhibitor of TGK and TAO. The complex structures of both enzymes with the inhibitors have been determined, providing a platform for further refinement of the trypanocidal potencies by structure–activity relationship studies. Conclusion: We have utilized rational design approach to identify novel trypanocidal compounds that may be used for the design of new class of anti-trypanosomal drugs for African trypanosomiasis. Disclosures: All authors: No reported disclosures.